Análise de perfis para atuar em negócios usando a tipologia de Carl Gustav Jung - Jung e o negociador - Patrocínio, Jose Antonio Camarinha (2007)
This work aims to be a helpful tool to identify wanted skills in business professionals. A model has been developed for this evaluation based in Jung s Theory of Psychological Types, witch tries to help how to identify the right talent by the predominant Junginian s profile. Also the work revisited the theory of authors that have influence the organization culture. An experiment with 232 people, being 99 as sales reps, 27 as business students and 106 project management students have been applied in order to investigate the effectiveness of this tool. In conclusion this work can be helpful as a reference for companies that need to identify the right persons to accomplish the necessary success for them